Folic acid conjugated carbon dots doped metal-organic framework materials for cell imaging. (December 2022) - Yang, J.; Cheng, Q.; Zhu, C.C.; Huang, H.Y.; Su, J.B.; Ni, W.; Ruan, B.; Ma, N.; Tsai, F.C.
Abstract: Folate receptor is one of the common biomarkers, which can be used for early diagnosis of cancer. Folic acid has bind specifically to folate receptor. Herein, folic acid is co-conjugated with carbon dots (FA-CDs) to achieve fluorescence imaging of tumor cells because CDs have excellent fluorescence properties, low toxicity, and good biocompatibility. In consideration of complex environment of organisms, metal-organic framework material as the host material is used for improving the stability of FA-CDs. In view of the negatively charged FA-CDs, positively charged UiO-66-NH2 was chosen as host material. Fluorescent CDs were synthesized from citric acid and urea using microwave method. And folic acid was conjugated with CDs by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide. FA-CDs@UiO-66-NH2 composite material was obtained by adsorption method, which had a great stability and anti-interference capability under different salt concentrations, pH, and coexistence substances. And FA-CDs@UiO-66-NH2 had low toxicity in both normal cells and tumor cells. Concurrently, composite material could realize fluorescence imaging in RAW cells and COS-7 cells, manifesting FA-CDs@UiO-66-NH2 possessed the capable of fluorescence imaging. Graphical abstract: The synthetic schematic diagram of FA-CDs@UiO-66-NH2 and (a) Bright field diagram of RAW cells incubated and (b) Fluorescence imaging of RAW cells at 405 nm excitation wavelength. (Scale Bar: 20 μm). Image 1 Highlights: Folic acid linked with carbon dots by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide. Metal-organic framework as host material can enrich guest materials and improve the stability of materials. Folic acid co-conjugated with carbon dots (FA-CDs)@UiO-66-NH2 have great stability and anti-interference capability. UiO-66-NH2 can enhance biocompatibility of FA-CDs, and FA-CDs@UiO-66-NH2 implement early diagnosis in tumor cells.